Innate defenses to intestinal cell death in necrotizing enterocolitis – spotlight on macrophage efferocytosis and its efficacy in rescuing inflamed intestinal mucosa - Kanuri, Sri Harsha; Bagang, Newly; Ulucay, Ayse Sena; Pandey, Popular; Singh, Gaaminpreet (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Necrotizing enterocolitis (NEC) is a grave gastrointestinal disease of preterm infants which is widely prevalent in the neonatal intensive care units. Current treatment options are very limited with high mortality and morbidity. With no disease specific interventions, understanding nascent cellular events that occur immediately after microbial insult can offer insights for devising novel treatment options for curtailing the disease progression in NEC. In this regard, intestinal cell death in NEC is a primordial cell-signaling event and is regarded as a harbinger of future pathological derangements such as increased intestinal permeability, intestinal dys-homeostasis, and systemic inflammation. Material and methods. We performed PubMed search of relevant articles that describes the host response to intestinal cell death in NEC by cellular battalion including dendritic cells, lymphocytes, neutrophils and macrophages which are important in containing intestinal inflammation. Analysis of the literature. We particularly focused this review on enumerating macrophage efferocytosis, and pertinent novel treatment modalities based on this physiological process that has inherent capability for down regulating inflammation and promoting tissue repair in NEC. We highlighted its mechanistic aspect including mediators, receptors and signaling mechanisms and its physiological significance. Conclusion. Macrophage efferocytosis is an overlooked and undervalued physiological defense mechanism to clear the dying intestinal epithelial cells for facilitating tissue healing and restoring the intestinal homeostasis. Any impairment of this critical defense mechanism can result in rapid clinical progression and systemic complications. Understanding its importance in the pathogenesis of NEC is important for designing novel therapeutic interventions to attenuate disease progression.
Keywords: efferocytosis; inflammation and immune responses; intestinal cell death; macrophage; necrotizing enterocolitis